Equity: In theory and practice - Young, H (Princeton University Press, 1994)
Identifies the specific rules and principles by which societies allocate common property and collective burdens among qualifying parties by examining the methods that people use to solve "everyday" distributive problems. Explores on how societies solve the distributive problems arising in seven illustrative cases: the demobilization of soldiers from the U.S. Army at the end of World War II; the allocation of kidneys among transplant patients; the apportionment of representation among political parties and states; the adjudication of conflicting property claims; the allocation of costs and benefits among participants in joint enterprises; the distribution of the tax burden; and the division of inheritances. Considers the common themes that cut across different areas of application and demonstrates how these pieces fit together into a larger picture. Young is Professor of Economics and Public Policy at the University of Maryland. Bibliography; index.